Identifikasi Kondisi Eksisting Fasilitas Prasarana Pendidikan di Lingkungan Universitas Cenderawasih - Yordan Yance Raweyai; Monita Yessy Beatrick; Juliani Wairata (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
To ensure mutual implementation of learning, supporting facilities, such as facilities and infrastructure, are needed. The availability of infrastructure, in terms of type, quantity, and quality, depends on the needs of each study program and its scientific characteristics. This type of research is descriptive research, namely exploring as much data as possible from the object being studied. Research aims to describe descriptively, summarizing various conditions found in the field or research objects.